A potential method for non-invasive acute myocardial infarction detection based on saliva Raman spectroscopy and multivariate analysis. (13th November 2015) - Cao, Gang; Chen, Maowen; Chen, Yuanxiang; Huang, Zufang; Lin, Jinyong; Lin, Jia; Xu, Zhihong; Wu, Shanshan; Huang, Wei; Weng, Guoxing; Chen, Guannan
Abstract: Raman spectroscopy (RS) was employed for human saliva biochemical analysis with the aim to develop a rapidly non-invasive test for acute myocardial infarction (AMI) detection. High-quality Raman spectra were obtained from human saliva samples of 46 AMI patients and 43 healthy controls. Significant differences in Raman intensities of prominent bands were observed between AMI and normal saliva. The tentative assignment of the observed Raman bands indicated constituent and conformational differences between the two groups. Furthermore, principal component analysis (PCA) combined with linear discriminant analysis (LDA) was employed to analyze and classify the Raman spectra acquired from AMI and healthy saliva, yielding a diagnostic sensitivity of 80.4% and specificity of 81.4%. The results from this exploratory study demonstrated the feasibility and potential for developing RS analysis of human saliva into a clinical tool for rapid AMI detection and screening.